2017
DOI: 10.1145/3073565
|View full text |Cite
|
Sign up to set email alerts
|

Cross Domain Recommender Systems

Abstract: Cross domain recommender systems (CDRS) can assist recommendations in a target domain based on knowledge learned from a source domain. CDRS consists of three building blocks: domain, user-item overlap scenarios, and recommendation tasks. The objective of this research is to identify the most widely used CDRS building-block definitions, identify common features between them, classify current research in the frame of identified definitions, group together research with respect to algorithm types, present existin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(21 citation statements)
references
References 101 publications
(106 reference statements)
0
19
0
Order By: Relevance
“…Apart from the gaps already mentioned in the above section, the study of Khan & Ibrahim [86] also pointed out future research directions for cross domain recommender systems. Those can be arranged into five groups, namely domain similarity enhancement, algorithm improvement, using of "big data" as a source domain, conventional recommender systems problems, and dataset extensions.…”
Section: Challenges and Open Issuesmentioning
confidence: 97%
See 1 more Smart Citation
“…Apart from the gaps already mentioned in the above section, the study of Khan & Ibrahim [86] also pointed out future research directions for cross domain recommender systems. Those can be arranged into five groups, namely domain similarity enhancement, algorithm improvement, using of "big data" as a source domain, conventional recommender systems problems, and dataset extensions.…”
Section: Challenges and Open Issuesmentioning
confidence: 97%
“…The study of Khan & Ibrahim [86] did a particularly good job at summarizing the literature in Cross Domain Recommendation Systems. The objective of this study was to identify the widely used CDRS building-block definition and to classify and visualize current CDRS research in the frame of identified building-block definitions.…”
Section: Transfer Learning In Recommender Systems 221 Summary Of LImentioning
confidence: 99%
“…Nowadays, users have multiple accounts on social networks. The data from multiple sites assist RS in reducing the cold-start problem [46][47][48][49][50][51]. Authors in [46] have worked in this direction to integrate cross-domain data.…”
Section: B Cross-domainmentioning
confidence: 99%
“…In another work, [22] use multi-view neural networks and propose a cross-domain RS to overcome the data sparsity problem. Recently, Khan et al [51] give a broad survey of cross-domain RSs.…”
Section: B Cross-domainmentioning
confidence: 99%
See 1 more Smart Citation